2023
DOI: 10.7554/elife.80529
|View full text |Cite
|
Sign up to set email alerts
|

Structural features stabilized by divalent cation coordination within hepatitis E virus ORF1 are critical for viral replication

Abstract: Hepatitis E virus (HEV) is an RNA virus responsible for over 20 million infections annually. HEV’s open reading frame (ORF)1 polyprotein is essential for genome replication, though it is unknown how the different subdomains function within a structural context. Our data show that ORF1 operates as a multifunctional protein, which is not subject to proteolytic processing. Supporting this model, scanning mutagenesis performed on the putative papain-like cysteine protease (pPCP) domain revealed six cysteines essen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Here, we found that the pORF1 polyprotein was unable to be processed auto-catalytically using a well-established in vitro transcription and translation system, in agreement with studies suggesting pORF1 cannot undergo proteolysis [ 17 , 46 ]. We, and others, have used this system to study the processing of many positive-sense RNA viruses.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we found that the pORF1 polyprotein was unable to be processed auto-catalytically using a well-established in vitro transcription and translation system, in agreement with studies suggesting pORF1 cannot undergo proteolysis [ 17 , 46 ]. We, and others, have used this system to study the processing of many positive-sense RNA viruses.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, our approach of separating domains with the support of a structural prediction of pORF1 resulted in a pattern largely fitting to what is described in literature. 24 , 38 , 39 The final separation took hinge regions separating well-defined regions into account. Overall, the HVR presented itself as the only domain lacking a proper secondary structure, which can be explained by repeated polyproline stretches flanking the visible, α-helical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis revealed that a number Reclovirids encode non-replicative proteins with other types of putative zinc-finger motifs. In particular, the ORF2 protein of Atriplex prostrata VLRA (Supplementary Table S1) contains the hexa-cysteine motif C(X6)C(X)C(XX)CXC(X12)C, which resembles unconventional hexa-cysteine motifs like those found in proteins of Hepatitis virus E and viruses of the genus Pestivirus [16,17], and in the small protein encoded by the ORF preceding TCMB in Colobanthus quitensis VLRA [7].…”
Section: Protein Domains and Motifs In Non-replicative Proteins Of Re...mentioning
confidence: 99%